2015
DOI: 10.1002/elan.201400718
|View full text |Cite
|
Sign up to set email alerts
|

Label‐Free Electrochemical Aptasensor for Determination of Chloramphenicol Based on Gold Nanocubes‐Modified Screen‐Printed Gold Electrode

Abstract: An ultrasensitive label‐free electrochemical aptasensor was developed for selective detection of chloramphenicol (CAP). The aptasensor was made using screen‐printed gold electrode modified with synthesized gold nanocube/cysteine. The interactions of CAP with aptamer were studied by cyclic voltammetry, square wave voltammetry (SWV) and electrochemical impedance spectroscopy. Under optimized conditions, two linear calibration curves were obtained for CAP determination using SWV technique, from 0.03 to 0.10 µM an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
28
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 67 publications
(29 citation statements)
references
References 41 publications
0
28
0
Order By: Relevance
“…Additionally, the sensor was tested for selectivity against interferes like kanamycin monosulfate, gentamycin sulfate, and oxytetracycline ( Figure 4 d), reproducibility, and stability when detected milk samples tetracycline. In another study, a label-free electrochemical aptasensor was fabricated using polyhedral-shaped Au nanocubes that were prepared via the seed-mediated method to act as electrochemical detective amplifiers for the detection of chloramphenicol antibiotic [ 72 ]. Selective chloramphenicol detection was achieved using a screen-printed electrode labeled with aptamer/AuNCs-cysteine.…”
Section: Antibiotics Electrochemical Detection Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Additionally, the sensor was tested for selectivity against interferes like kanamycin monosulfate, gentamycin sulfate, and oxytetracycline ( Figure 4 d), reproducibility, and stability when detected milk samples tetracycline. In another study, a label-free electrochemical aptasensor was fabricated using polyhedral-shaped Au nanocubes that were prepared via the seed-mediated method to act as electrochemical detective amplifiers for the detection of chloramphenicol antibiotic [ 72 ]. Selective chloramphenicol detection was achieved using a screen-printed electrode labeled with aptamer/AuNCs-cysteine.…”
Section: Antibiotics Electrochemical Detection Methodsmentioning
confidence: 99%
“…The sensor was found to be promising for chloramphenicol sensing in human serum with improved repeatability, selectivity, stability, and sensitivity. This research group detected chloramphenicol using label-free electrochemical aptasensors based on Au nanostructures in two successive works [ 72 , 73 ]. The same group after that was detected epirubicin selectively using label-free electrochemical aptasensor [ 74 ].…”
Section: Antibiotics Electrochemical Detection Methodsmentioning
confidence: 99%
“…Like the other antibiotics, there are more reports of constructed electrochemical aptasensors for the detection of chloramphenicol [ 41 , 49 , 112 , 164 , 165 , 166 , 167 , 168 , 169 , 170 , 171 , 172 , 173 , 174 , 175 ] As shown in Table 9 , the lowest LOD could be obtained using the proposed electrochemical aptasensor based on Y-shaped DNA probes [ 174 ]. These probe-based metal ions encoded the nanoscale metal-organic frameworks (NMOF) as a substrate, and a circular strand-replacement DNA polymerization (CSRP) target triggered the amplification strategy.…”
Section: Aptasensors For Different Antibiotic Classesmentioning
confidence: 99%
“…Cur has therapeutic or prophylactic potential against multiple human diseases, such as Alzheimer's disease, cancer, cardiovascular diseases and other inflammatory diseases. Spectroscopic evidence showed that Cur binds to the major and minor grooves of nucleic acid duplex through thymine (minor groove), guanine and adenine (major groove) by hydrogen bonding . If Epi captured by the aptamer, it will decline the degree of connectivity of complementary strand to the aptamer, as a result decreasing the redox signal of Cur.…”
Section: Introductionmentioning
confidence: 99%